Retraced memories - virtual reconstruction of an architectural landmark - Simone Fallica; Raissa Garozzo; Cettina Santagati (Virtual Archaeology Review, 2021)
This paper addresses the challenge of digitally reconstructing ruined architectural sites and retracing their history, in order to virtually recompose their geometrical, stylistic and material integrity. To this end, the research team analyzed the ruins of the church of Santa Maria de Monasterio Albo, located in the ancient village of Misterbianco (Sicily) and destroyed (together with the entire hamlet) by the 1669 eruption of Mount Etna. In the last years, some excavation campaigns brought the church to the light, unveiling the remains of the main portal and six altars, which are one of the most remarkable examples of Mannerist art in eastern Sicily. This research aimed to three-dimensional (3D) reconstruct both the altars and the portal, ideally reviving their original 17th century configuration. This goal was achieved through an in-depth archival research (documents dating back to the years between 1300 and 1666 were consulted), an analysis of Classic and Renaissance treatises, and two integrated digital survey campaigns (laser scans and photogrammetry). The outcome is represented by the 3D models of the seven artifacts, which include surviving parts reconstructed as photogrammetric meshes, several fragments were placed in their likely early location through a virtual anastylosis, and NURBS (Non Uniform Rational Basis-Splines) surfaces (recreating the no longer existing elements). The latter were 3D modelled based on the treatises (which provided information on the correct proportioning) or in analogy with other coeval similar artifacts. Overall, the digital reconstruction was based on the ethical principles of transparency of the intervention, recognition of non-original additions and distinction between evidence and hypothesis, according to the London Charter and the Seville Principles. The experimentation provides a valid support for possible interventions in the real world and is the starting point to develop a digital archive of the site, which would make the different accuracy levels the reconstruction explicit.